2009
DOI: 10.1007/s11249-009-9457-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Transfer Film on the Friction and Wear of Metal Carbide Reinforced Amorphous Carbon Coatings During Run-in

Abstract: The relationship between friction, wear, and transfer films of three metal carbide-reinforced amorphous carbon coatings (TiC/a:C, TiC/a:C-H, and WC/a:C-H), sometimes referred to as metal-doped diamond-like carbon coatings, has been investigated. Tribological tests were performed in an in situ tribometer with sapphire or steel hemispheres run against coated flats in dry or ambient air. The sliding contact interface was observed and recorded by optical microscopy during reciprocating sliding tests. The friction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(52 citation statements)
references
References 43 publications
1
51
0
Order By: Relevance
“…The sand particles thus become lost in the ridge and could not cause further abrasion [25]. Scharf and Singer [26] indicated that the wear loss of the coatings were independent of counterbody material, it is clear that friction and wear were controlled by the transfer film formed on couterbody, and not by the counterbody. Therefore, the formation of the ridge on the contact area could be the main reason for such low wear rate and friction coefficient of a-C:H film under sand-dust conditions.…”
Section: The Worn Surface Morphologies Of A-c:h Film and Counterbody Pinmentioning
confidence: 99%
“…The sand particles thus become lost in the ridge and could not cause further abrasion [25]. Scharf and Singer [26] indicated that the wear loss of the coatings were independent of counterbody material, it is clear that friction and wear were controlled by the transfer film formed on couterbody, and not by the counterbody. Therefore, the formation of the ridge on the contact area could be the main reason for such low wear rate and friction coefficient of a-C:H film under sand-dust conditions.…”
Section: The Worn Surface Morphologies Of A-c:h Film and Counterbody Pinmentioning
confidence: 99%
“…3 The velocity accommodation modes of a transfer layer; (a) shear and extrusion of debris, and (b) interfacial sliding, based on Refs. [43,44]. now focus on the friction of DLC coatings in a water environment, to examine the potential for the use of DLC coatings on components under aqueous lubrication.…”
Section: Transfer Layer Formationmentioning
confidence: 99%
“…The fall in friction occurs as a transfer layer forms in the contact composed of worn debris from the DLC coating and steel ball. The mechanism for this has been described by Scharf and Singer [20,24]. The coefficient of friction increases again as the wear debris reacts with oxidative species in the environment, resulting in higher adhesion.…”
Section: Friction and Wearmentioning
confidence: 93%